Question

(a) Compute the values of \( u_{1} \) and \( u_{2} \) when the difference equations and initial values are as given below. (i) \( u_{n+1}=4 u_{n}\left(u_{n}-5\right), u_{0}=7 \) (ii) \( u_{n+1}=\frac{u_{n}}{3}-\frac{1}{2 u_{n}}, u_{0}=1 \).

Ask by Flynn Santiago. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( u_1 = 56 \) and \( u_2 = 11424 \) for the first problem, and \( u_1 = -\frac{1}{6} \) and \( u_2 = \frac{53}{18} \) for the second problem.

Solution

Let's compute the values of \( u_1 \) and \( u_2 \) for each of the given difference equations. ### (i) \( u_{n+1} = 4 u_n (u_n - 5) \) with \( u_0 = 7 \) 1. **Compute \( u_1 \):** \[ u_1 = 4 u_0 (u_0 - 5) = 4 \times 7 \times (7 - 5) = 4 \times 7 \times 2 = 56 \] 2. **Compute \( u_2 \):** \[ u_2 = 4 u_1 (u_1 - 5) = 4 \times 56 \times (56 - 5) = 4 \times 56 \times 51 \] \[ 56 \times 51 = 2856 \quad \text{(since } 56 \times 50 = 2800 \text{ and } 56 \times 1 = 56\text{)} \] \[ u_2 = 4 \times 2856 = 11424 \] **Results for (i):** - \( u_1 = 56 \) - \( u_2 = 11424 \) --- ### (ii) \( u_{n+1} = \frac{u_n}{3} - \frac{1}{2 u_n} \) with \( u_0 = 1 \) 1. **Compute \( u_1 \):** \[ u_1 = \frac{u_0}{3} - \frac{1}{2 u_0} = \frac{1}{3} - \frac{1}{2 \times 1} = \frac{1}{3} - \frac{1}{2} = -\frac{1}{6} \] 2. **Compute \( u_2 \):** \[ u_2 = \frac{u_1}{3} - \frac{1}{2 u_1} = \frac{-\frac{1}{6}}{3} - \frac{1}{2 \times \left(-\frac{1}{6}\right)} = -\frac{1}{18} + 3 = \frac{53}{18} \] \[ \text{(Since } 3 = \frac{54}{18} \text{ and } \frac{54}{18} - \frac{1}{18} = \frac{53}{18}\text{)} \] **Results for (ii):** - \( u_1 = -\frac{1}{6} \) - \( u_2 = \frac{53}{18} \) --- **Final Answer:** Problem i Answer:  \( u_{1} = 56 \) and \( u_{2} = 11424 \). Problem ii Answer:  \( u_{1} = -\dfrac{1}{6} \) and \( u_{2} = \dfrac{53}{18} \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To find the values of \( u_{1} \) and \( u_{2} \) for the given difference equations, we will substitute the initial values \( u_{0} \) into the recurrence relations to compute each subsequent term. (i) For the equation \( u_{n+1}=4 u_{n}\left(u_{n}-5\right) \) with \( u_{0}=7 \): 1. **Calculate \( u_{1} \)**: \[ u_{1} = 4 u_{0} (u_{0} - 5) = 4 \cdot 7 (7 - 5) = 4 \cdot 7 \cdot 2 = 56 \] 2. **Calculate \( u_{2} \)**: \[ u_{2} = 4 u_{1} (u_{1} - 5) = 4 \cdot 56 (56 - 5) = 4 \cdot 56 \cdot 51 = 11424 \] Thus, for \( u_{0}=7 \), we have \( u_{1} = 56 \) and \( u_{2} = 11424 \). (ii) For the equation \( u_{n+1}=\frac{u_{n}}{3}-\frac{1}{2 u_{n}} \) with \( u_{0}=1 \): 1. **Calculate \( u_{1} \)**: \[ u_{1} = \frac{u_{0}}{3} - \frac{1}{2 u_{0}} = \frac{1}{3} - \frac{1}{2 \cdot 1} = \frac{1}{3} - \frac{1}{2} \] To get a common denominator (which is 6), we have: \[ u_{1} = \frac{2}{6} - \frac{3}{6} = -\frac{1}{6} \] 2. **Calculate \( u_{2} \)**: \[ u_{2} = \frac{u_{1}}{3} - \frac{1}{2 u_{1}} = \frac{-\frac{1}{6}}{3} - \frac{1}{2 \left(-\frac{1}{6}\right)} = -\frac{1}{18} + 3 = \frac{-1 + 54}{18} = \frac{53}{18} \] Thus, for \( u_{0}=1 \), we have \( u_{1} = -\frac{1}{6} \) and \( u_{2} = \frac{53}{18} \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy